The Role of the IL-23/IL-17 Axis in Disease Initiation in Spondyloarthritis: Lessons Learned From Animal Models - Mandour, Mohamed; Chen, Sijia; van de Sande, Marleen G. H. (Frontiers in Immunology, 2021)
Spondyloarthritis (SpA) is a spectrum of chronic inflammatory joint diseases that frequently presents with inflammation of the axial skeleton, peripheral joints, entheses, skin, and gut. Understanding SpA pathogenesis has been proven challenging due to the limited availability of human target tissues. In recent years, the interleukin (IL)-23/IL-17 pathway has been implicated in the pathogenesis of SpA, in addition to the Tumor Necrosis Factor Alpha (TNF-α) cytokine. The underlying molecular mechanisms by which the IL-23/IL-17 pathway triggers disease initiation, both in the joints as well as at extra-musculoskeletal sites, are not precisely known. Animal models that resemble pathological features of human SpA have provided possibilities for in-depth molecular analyses of target tissues during various phases of the disease, including the pre-clinical initiation phase of the disease before arthritis and spondylitis are clinically present. Herein, we summarize recent insights gained in SpA animal models on the role of the IL-23/IL-17 pathway in immune activation across affected sites in SpA, which include the joint, entheses, gut and skin. We discuss how local activation of the IL-23/IL-17 axis may contribute to the development of tissue inflammation and the onset of clinically manifest SpA. The overall aim is to provide the reader with an overview of how the IL-23/IL-17 axis could contribute to the onset of SpA pathogenesis. We discuss how insights from animal studies into the initiation phase of disease could instruct validation studies in at-risk individuals and thereby provide a perspective for potential future preventive treatment.